Upaya Guru IPS dalam Meningkatkan Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran IPS Kelas VIII di SMPN 1 Sumbergempol - Irna Firdausil Ma’wa (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
Critical thinking skills are essential for students to be able to analyze, evaluate, and solve problems systematically. However, during learning, many students still have difficulty in developing these skills, which can be caused by less interactive learning methods and the lack of implementation of effective teaching strategies. This study aims to determine the efforts of social studies teachers in improving critical thinking skills of grade VIII students at SMPN 1 Sumbergempol. This study is a type of case study research. Data collection techniques used are observation, interviews and documentation. This study shows that the efforts made by teachers in improving students' critical thinking in social studies learning are to give students a problem and they must solve the problem, in addition, the use of strategies, methods, models, and learning media also have an effect on improving students' critical thinking, especially in social science learning.